Сборник задач по бухгалтерскому учету в общественном питании: учебное пособие для вузов / А. Д. Зыков, Н. А. Наумова - Зыков Анатолий Дмитриевич (1975)
Экземпляры: КХ (20170714) / Инвентарный номер: 622837 / Сис.шифр: 338Т8 / Авт.знак: З-96 / ГРНТИ: 06 / ББК: 65